1991
DOI: 10.1210/endo-128-1-623
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor as a Potent Inhibitor of Adrenocorticotropin-Induced Cortisol Production and Steroidogenic P450 Enzyme Gene Expression in Cultured Human Fetal Adrenal Cells*

Abstract: We have previously demonstrated that tumor necrosis factor alpha (TNF-alpha), a multifunctional cytokine mainly produced by activated monocytes, inhibits the ACTH-induced production of cortisol in cultures of human fetal adrenals. To clarify the molecular basis of this suppression, we investigated the effect of recombinant TNF-alpha (rTNF-alpha) on the messenger RNAs (mRNAs) for adrenal cytochrome P450 oxidases, P450scc (cholesterol side-chain cleavage enzyme/20.22-desmolase), P450c11 (11 beta-hydroxylase/18-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(50 citation statements)
references
References 38 publications
1
48
0
1
Order By: Relevance
“…A number of mechanisms may be responsible. TNFa reduces adrenal cortisol synthesis by reducing the sensitivity of adrenal receptors to ACTH resulting in a blunted response to cosyntropin and high ACTH levels with relatively low cortisol levels in the setting of acute illness (35). In addition, corticostatins or defensins produced by cells, such as macrophages and neutrophils, and which may proliferate in a systemic inflammatory response, inhibit the steroidogenic activity of ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…A number of mechanisms may be responsible. TNFa reduces adrenal cortisol synthesis by reducing the sensitivity of adrenal receptors to ACTH resulting in a blunted response to cosyntropin and high ACTH levels with relatively low cortisol levels in the setting of acute illness (35). In addition, corticostatins or defensins produced by cells, such as macrophages and neutrophils, and which may proliferate in a systemic inflammatory response, inhibit the steroidogenic activity of ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of TNF and of its receptors within the adrenal glands suggests that this cytokine plays a role in adrenal function, even though experiments found variably stimulatory [43,44] or inhibitory [45,46] effects of TNF on steroidogenesis. Likewise, IL-1 and its receptor are also produced in the adrenal glands and contribute to steroidogenesis at least partly by regulating prostaglandin pathways [47].…”
Section: Cytokine-induced Activation Of the Hpa Axismentioning
confidence: 99%
“…However, there are dozens of additional hormones, neuropeptides, and cytokines involved in this regulation. Proinflammatory cytokines TNF (Jäättelä et al 1990, 1991, Ilvesmäki et al 1993, Voutilainen 1998, Judd et al 2000, Mikhaylova et al 2007), IL6 , Judd et al 2000, and IL1B have been shown to modulate bovine, murine, and human adrenal steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%